Biogeographic regionalization by spatial and environmental components: Numerical proposal. - Mayra Flores-Tolentino (Public Library of Science (PLoS), 2021)
Regionalization through the analysis of species groups offers important advantages in conservation biology, compared to the single taxon approach in areas of high species richness. We use a systematic framework for biogeographic regionalization at a regional scale based on species turnover and environmental drivers (climate variables and soil properties) mainly of herbaceous plant species richness. To identify phytogeographic regions in the Balsas Depression (BD), we use Asteraceae species, a family widely distributed in Seasonally Dry Tropical Forest (SDTF) and the most diverse of the vascular plants in Mexico. Occurrence records of 571 species were used to apply a quantitative analysis based on the species turnover, the rate of changes in their composition between sites (β-Simpson index) and the analysis of the identified environmental drivers. Also, the environmental predictors that influence species richness in the SDTF were determined with a redundancy analysis. We identified and named two phytogeographic districts within the SDTF of the BD (Upper Balsas and Lower Balsas). According to the multi-response permutation procedure, floristic composition of the two districts differs significantly, and the richness of exclusive species in Upper Balsas was higher (292 species) than in the Lower Balsas (32 species). The proportion of Mg and Ca in the soil and the precipitation of the driest three-month period were the environmental factors with greatest positive influence on species richness. The division of geographic districts subordinated to the province level, based on diverse families such as Asteraceae, proved to be appropriate to set up strategies for the conservation of the regional flora, since at this scale, variation in species richness is more evident. Our findings are consistent with a growing body of biogeographic literature that indicates that the identification of smaller biotic districts is more efficient for the conservation of biodiversity, particularly of endemic or rare plants, whose distribution responds more to microhabitats variation.